Effects of Cooperative Learning on Achievements in Arabic Writing and Social Skills for form Two Students in Selangor, Malaysia - Kirembwe, R. A. H. (2004)
This experimental research investigated the problem among students of Arabic as a second language in Malaysian secondary schools in applying Arabic writing rules in their writing tasks. The problem was based on the unique factors of Arabic writing skills and an unsystematic application of general academic writing skills which caused low scores among students in their Arabic as a second language paper. Also, the study determined the relationship between learners’ social skills and their achievements in Arabic writing papers. The study compared between the effectiveness of Cooperative Integrated Reading and Composition with Teacher-Centered instruction method. The Solomon Randomized Four Group Design was used as a basis of the experiment. The results of this study showed significant differences in mean scores on Arabic writing skills 1 - 2 = 4.26, t (151) = 2.872, p < .05; SD = 0.26 at α2. None of the investigated relationship was found significant between the mean scores on Arabic writing skills and mean scores on students' social skills. However, the results showed an overall significant correlation r = .71 in determining the relationship between achievement in Arabic writing and students' social skills. The discussion focussed on applicability of the research findings. Recommendations provided were based on the research findings.